Caso de estudio: IOI's global challenge: moving up the palm oil value chain - Cáceres Ruiz, Javier Fernando (2019)
The present work seeks to analyse the 5 main areas: international market intelligence, international marketing, strategic global management, international trade logistics and international finance of IOI Corporation Berhad (IOI), to assess their situation in the global market of the palm oil industry. The case study focuses on the 2012-2017 period, evaluating the main changes in the strategy driven by its Loders Croklaan division and its expansion to several markets. Subsequently, the company was affected by losses in exchange rates and negative externalities, such as the phenomenon of “El Niño” and the suspension of its RSPO certifications; which triggered a crisis of the company over which the CEO sought to implement changes in IOI strategies as a multinational group. Through a quantitative analysis of the IOI group and its main competitors in the industry, the main products and markets for palm oil were identified, as well as the main customer segments and their respective distribution channels. On the other hand, the main communication strategies of the group against negative externalities were identified, as well as the internal and external qualities of the company against current opportunities and threats in the industry. Likewise, the main characteristics of IOI as a family business, and its influence on the international strategy of the company were analysed. Similarly, the main variables of its supply chain after IOI expanded to different markets, the effect of the integration of diverse business units (downstream), and the main adversities of concentrating the supply chain of its upstream businesses in Malaysia and Indonesia were identified. Finally, the company's financial results were analysed from 2012 to 2017, and they were also projected based on the strategies to be implemented in the company's finances by 2025.